Escala de Medo da COVID-19 – Validação e adaptação para o Período Perinatal - Monalisa Nascimento dos Santos Barros; M. Aguiar; F. Carvalho; A. Macedo; A.T. Pereira (2021)
It aims to analyze the psychometric properties of the COVID-19 Fear Scale in the perinatal period, consisting of two additional items for the perinatal period. The research was registered with CONEP. 204 pregnant women with an average age of 30.12 years (± 5.45) and an average gestational age of 25.17 (± 6,553) answered the questionnaires through social networks in Brazil. We used SPSS Statistics, used for parametric measurements, Pearson's coefficient and Student's non-parametric T - Mann Whitney U and for the magnitude of the correlation coefficients with perinatal anxiety and depressive symptoms, Cohen's criteria. AMOS 26.0 was used for confirmatory factor analysis. For internal consistency, Cronbach's alpha. The results indicate that EMC-19-9 is a one-dimensional construct, has robust psychometric qualities, very good internal consistency of the questionnaire and shows convergent validity, has a moderate and significant correlation with perinatal anxiety and a significant, albeit slight, correlation with perinatal depression.The total scores were comparable at all ages, which suggests that it is a good psychometric instrument to be used in assessing COVID-19 fears among pregnant women in Brazil. Future studies should also assess association with underlying medical conditions associated with greater fear.